A Drosophila model of mitochondrial disease caused by a complex I mutation that uncouples proton pumping from electron transfer - Jonathon L. Burman (2018)
© 2014, Company of Biologists Ltd. All rights reserved. Mutations affecting mitochondrial complex I, a multi-subunit assembly that couples electron transfer to proton pumping, are the most frequent cause of heritable mitochondrial diseases. However, the mechanisms by which complex I dysfunction results in disease remain unclear. Here, we describe a Drosophila model of complex I deficiency caused by a homoplasmic mutation in the mitochondrial-DNA-encoded NADH dehydrogenase subunit 2 (ND2 ) gene. We show that ND2 mutants exhibit phenotypes that resemble symptoms of mitochondrial disease, including shortened lifespan, progressive neurodegeneration, diminished neural mitochondrial membrane potential and lower levels of neural ATP. Our biochemical studies of ND2 mutants reveal that complex I is unable to efficiently couple electron transfer to proton pumping. Thus, our study provides evidence that the ND2 subunit participates directly in the proton pumping mechanism of complex I. Together, our findings support the model that diminished respiratory chain activity, and consequent energy deficiency, are responsible for the pathogenesis of complex-I-associated neurodegeneration.